(3GdNjQ GdhGaQ ajeG dehdGfG GdSdWGf ef GdefGbH hGdeBKQs
(3ChdgG (B:s
(3GdMeO ddg QHj HGQF GdfSe Ld Gdegjef Ph GdELdGd hGdYXe s
(3BNQgG (B:s
(3hMSHfG Gddg QH GdYQT NGdbfG fYe Gdhcjd Edg eafj GdCee s
(3hgj bUjOI aj eOM GdCTQa bGjJHGjs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B2 - (3U (B292 s
(3eUOQ GbJfGA GdCUd (B:s
(3CjG UhajG (B((3Yf fSNI GdeLeY GdYdej GdYQGbj(B) (139) s
Keywords: (3GdCOHs